Polarization fatigue in antiferroelectric (Pb, La)(Zr, Ti)O3 thin films: The role of the effective strength of driving waveform. (July 2015) - Geng, Wenping; Liu, Yang; Lou, Xiaojie; Zhang, Fuping; Liu, Qida; Dkhil, Brahim; Zhang, Ming; Ren, Xiaobing; He, Hongliang; Jiang, Anquan
Abstract: In this study, a critical parameter termed as "effective electric strength" is developed to depict polarization fatigue in antiferroelectric thin films. Specifically, the effect of pulse width, frequency, and magnitude of driving voltage (or field) on polarization fatigue of antiferroelectric (Pb, La)(Zr, Ti)O3 (PLZT) thin films was investigated in detail. By transforming all the waveforms with different pulse-widths/voltages/frequencies into their effective electric strength, a strong correlation between the effective strength and the degree of polarization fatigue in the PLZT films is revealed. For instance, it was found that appreciable fatigue usually occurs when the effective strength is larger than or equal to the voltage of phase transition from antiferroelectric phase to ferroelectric phase. In addition, it is shown that the films are more prone to fatigue for a lower frequency of the same effective strength. Our findings could be well explained in the framework of the local phase decomposition arising from switching induced charge injection.